SAMUEL TAYLOR COLERIDGE'S ROLE IN CRITICISM - Farmanov Gayrat (PEDAGOGS, 2024)
Abstract; Coleridge is concerned with the philosophy and science of his time. was the dominant opinion on many issues, as John Stuart Mill acknowledged, along with others who studied the history of romanticism. as it becomes more manifest in external facts, it becomes a symbol of things proportionately more important